Identifikasi Karakter Morfologis Dan Hubungan Kekerabatan Beberapa Genotipe Kelapa (Cocos nucifera L.) Di Kabupaten Langkat Sumatera Utara - ADITYA PRAKOSO; Hot Setiado; Lollie Agustina P.Putri (Jurnal Agroekoteknologi, 2019)
Identification of morphological characteristics and phylogenic relationship used to identify the best coconut characters that can be used as elders and germplasm. The purpose of this research was to identify the morphological characteristics and phylogenetic relationship of several genotypes of coconut in Pangkalan Brandan districts, Pangkalan Susu districts and Sei Bingei districts Langkat regency North Sumatera. The research was conducted from April to Mei 2018 by descriptive survey method based on coconut descriptor of International Plant Genetic Resources Institute (IPGRI) using accidental sampling. This result showed that in research area there were 13 genotypes of dwarf coconut and 14 genotypes of tall coconut. The morphological characteristics were  found for crown shape viz (spherical, hemispherical, X-shaped ‘silhouette’), flower shape (normal and additional spathes or bracts), and fruit size (ovoid, almost round, oblate). The closet phylogenetic relaationship is AP16 and AP2 with coefficient euclidean 3,464 and farthest phylogenetic relationship is AP20 and AP22 with coefficient euclidean 10,488. Phylogenetic relationship of between genotypes of coconut in Pankalan Brandan Districts, Pangkalan Susu Districts and Sei Bingei Districts Langkat regency still have a close level relationship. Keyword : coconut, morphological characteristics, phylogenic relationship, Langkat regency